Water Problems in The Central Asian Republic and Its Importance in Its Relations - Turdimuratova Jamila Mirzamuratovna (Zien Journals, 2021)
This article discusses the problems of water in the Central Asian republics and its importance in relations. This problem has been systematically analyzed and the literature has been analyzed.
Keywords: United Nations; Central Asia; water issues; water demand